2004
DOI: 10.1007/s00216-004-2493-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oil and water content in olive pomace using near infrared and Raman spectrometry. A comparative study

Abstract: Near infrared (NIR) reflectance and Raman spectrometry were compared for determination of the oil and water content of olive pomace, a by-product in olive oil production. To enable comparison of the spectral techniques the same sample sets were used for calibration (1.74-3.93% oil, 48.3-67.0% water) and for validation (1.77-3.74% oil, 50.0-64.5% water). Several partial least squares (PLS) regression models were optimized by cross-validation with cancellation groups, including different spectral pretreatments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 13 publications
2
41
2
1
Order By: Relevance
“…Furthermore, NIRS determinations of oil content and humidity in olive paste and olive pomace obtained comparable efficiency to already well established methodologies such as nuclear magnetic resonance and the Soxhlet extraction method (García et al, 2005;Conte et al, 2003;Muik et al, 2004;Gallardo et al, 2005). Previously, Hermoso et al (1999) reported calibration coefficients for determining the oil content and the humidity of R ϭ 0.96 and R ϭ 0.60, respectively, in olive cakes resulting from the two phases oil NIR prediction of fruit moisture, free acidity and oil content in intact olives Por José Antonio Cayuela 1* , José María García 1 and Nuria Caliani extraction system, using NMR as the reference analytical method.…”
Section: Introductionsupporting
confidence: 58%
“…Furthermore, NIRS determinations of oil content and humidity in olive paste and olive pomace obtained comparable efficiency to already well established methodologies such as nuclear magnetic resonance and the Soxhlet extraction method (García et al, 2005;Conte et al, 2003;Muik et al, 2004;Gallardo et al, 2005). Previously, Hermoso et al (1999) reported calibration coefficients for determining the oil content and the humidity of R ϭ 0.96 and R ϭ 0.60, respectively, in olive cakes resulting from the two phases oil NIR prediction of fruit moisture, free acidity and oil content in intact olives Por José Antonio Cayuela 1* , José María García 1 and Nuria Caliani extraction system, using NMR as the reference analytical method.…”
Section: Introductionsupporting
confidence: 58%
“…In multivariate calibrations, the samples of vegetable oils were independently separated into calibration and validation data sets, respectively. The separation into data sets is carried out in order to get the similar standard deviation and average values so that both data sets spanned the working range of the studied vegetable oils [14]. The overlay of calibration spectra composed from EVOO, GSO, RBO and WO in quaternary mixtures with the composition as shown in Table 1 was depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OP chemical composition is generally characterized by a high content of crude fiber and sugars (mainly polysaccharides) and moderate values of crude protein, fatty acids (oleic acid 18:1ω-9), polyalcohols, polyphenols and other pigments (Borja, Martín, Rincón, & Raposo, 2003;Brunetti et al, 2005;Muik, Lendl, Molina-Díaz, Pérez-Villarejo, & Ayora-Cañada, 2004;Saviozzi, Levi-Minzi, Cardelli, Biasci, & Riffaldi, 2001). A variety of substances with proven antioxidant and radical scavenging activity, such as hydroxytyrosol (3, 4 -DHPEA), tyrosol (p-HPEA) and their secoiridoid derivatives (dialdheydic form of decarboxymethyl elenolic acid, 3, 4 -DHPEA-EDA or p-HPEA-EDA) as well as verbascoside, is also contained in OP (Amro, Aburjai, & Al-Khalil, 2002) However, the chemical composition of OPs may vary widely in relation to the agronomic and technological conditions of production.…”
Section: Op's Sources and Nutritional Valuementioning
confidence: 99%